A Traceability System for Sulfonamide Residues in Chicken Meat-Balls - Mohammad Rashedi, Ismail Fitry (2008)
Studies on the effect of different temperature and time for boiling and deep-frying, and power and time for micro-waving on sulfonamides (SAs) residues i.e. sulfadiazine (SDZ), sulfamethazine (SMZ), sulfamethoxazole (SMX), and sulfaquinoxaline (SQX) in chicken meat-balls were carried out. The purpose was to use the data collected to develop a traceability system model for SAs residues. Blank chicken meat was fortified with the mixed SAs standard and chicken meat-balls were produced. The cooking methods were conducted consecutively from boiling, deep-frying and micro-waving. Several methods were evaluated for the analysis of the SAs residues in the chicken meat-balls, which resulted in acceptable range of recoveries, from 82.0 to 98.9 % and RSDs from 0.7 to 7.6 %. The chromatogram of both the raw chicken meat and the chicken meat-balls showed no interfering peaks from other compounds present in the SAs analysis. Boiling of chicken meat-balls showed that temperature needs to be at 100 °C to obtain significant reduction (p<0.05) compared to 80 and 90 °C. A significant reduction (p<0.05) was observed at boiling for 6 min. In deep-frying study, significant reduction (p<0.05) of SAs concentrations was observed against the control for temperature factor. Significant reductions (p<0.05) of SAs concentrations among all the treatments and against the control were observed for the time factor. In micro-waving, the power and time factor showed various effects on reducing SAs residues in chicken meat-balls. Pearson correlation coefficient showed that time had greater effect compared to temperature on the reduction of SAs concentration upon boiling and deep-frying. Power had greater effect on micro-waving process compared to time. The SAs concentration was reduced at the same time the internal temperature increased during boiling and deep-frying. There were negative correlations for deep-frying and micro-waving between the SAs concentration and weight changes parameters. Analyses on the Reducing Half Life (RHL) showed that microwaving processes had the shortest RHL of SAs followed by deep-frying and boiling processes. The RHL for the three cooking methods were from 0.9 to 83.9 min. The traceability system model was developed by using the Visual Basic 6.0 software with the percentage of reduction and linear regression were applied as the main method for detection of SAs residues. The first detection method for the traceability system model was based on the actual percentage reductions data of SAs residues. The percentage of reductions for every SAs at different cooking method were recorded earlier from the chemical analysis and calculated to be keyed in into the system. The second detection method to track and trace the SAs residue was by using the linear regressions developed from the result of effect of cooking methods. The equations of the linear regressions were determined from the data collected and inserted into the traceability system to be used for prediction of the SAs amount. The traceability system can be used to monitor the MRLs of the SAs before and after the processing, which will make the screening and monitoring work easier for the regulatory agencies, industry workers and consumers. The system could be used to gain the confidence on the safety of the chicken meat-balls from SAs residue and also could be applied for other type of veterinary drugs and pesticides residues.